2016
DOI: 10.3390/rs8050394
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Aerosol Optical and Micro-Physical Properties over Northeast Asia from a Severe Dust Storm in April 2014

Abstract: This study focuses on analyzing the changes to aerosol properties caused by the dust storm called "China's Great Wall of Dust" that originated from the Taklimakan Desert in April 2014. IDDI (Infrared Difference Dust Index) images from FY-2E and true color composite images from FY-3C MERSI (Medium Resolution Spectral Imager) show the breakout and transport path of the dust storm. Three-hourly ground-based measurements from MICAPS (Meteorological Information Comprehensive Analysis and Process System) suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…These high winds may also raise the local dust. A severe dust storm which originated from the Taklamakan Desert occurred in late April 2014 (Fang et al , ). Forwards air mass trajectories starting from the Taklamakan Desert during the dust storm were modelled by Fang et al () and the results showed the dust transport paths and affected areas which included the source regions of the Yangtze River.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These high winds may also raise the local dust. A severe dust storm which originated from the Taklamakan Desert occurred in late April 2014 (Fang et al , ). Forwards air mass trajectories starting from the Taklamakan Desert during the dust storm were modelled by Fang et al () and the results showed the dust transport paths and affected areas which included the source regions of the Yangtze River.…”
Section: Resultsmentioning
confidence: 99%
“…A severe dust storm which originated from the Taklamakan Desert occurred in late April 2014 (Fang et al , ). Forwards air mass trajectories starting from the Taklamakan Desert during the dust storm were modelled by Fang et al () and the results showed the dust transport paths and affected areas which included the source regions of the Yangtze River. In this study, backwards trajectories with the hybrid single particle Lagrangian integrated trajectory (HYSPLIT) model combined with vertical profile products from cloud‐aerosol lidar infrared pathfinder satellite observations (CALIPSO) were used to further analyse the influence of the dust storm from the Taklamakan Desert on the source regions of the Yangtze River.…”
Section: Resultsmentioning
confidence: 99%
“…Dust storms usually occur in the arid and semi-arid areas of the desert and its surrounding area in late winter and early spring [32][33][34][35]. North Africa, the Middle East, Middle and South Asia, East Asia, North America, and Australia are dust storm prone areas, where Western China is part of the Middle Asia dust storm prone area, and Northern China is part of the East Asia dust storm prone area [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…It processes kinds of meteorological information such as ground observation data, aerological sounding data, satellite cloud data, numerical forecast data, radar data, typhoon path data, urban forecast data, etc. MICAPS supports a medium-term, short-term, and instant weather forecast platform by retrieving various meteorological data, showing the meteorological graphics and images as well as the processing and editing images [34,39,40].…”
Section: Introduction To Validation Datamentioning
confidence: 99%
“…(2019); Cyprus, Mamouri and Ansmann (2014); United States, Prospero (1999); Northeast Asia, Fang et al. (2016); East Asia, Liu et al. (2019); China, Xie et al.…”
Section: Introductionmentioning
confidence: 99%